ANALISIS KINERJA PEGAWAI BIDANG MINERAL DAN BATUBARA PADA DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI RIAU (STUDI KASUS IZIN USAHA PERTAMBANGAN PASCA UU NO. 23 TAHUN 2014) - Fifin Alfianata (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Employee performance is the result of someone working in an organization. Performance appraisal should be in view of how it works as far as where the goal is reached. The performance of the employees of the Department of Mineral and coal unit at energy and Mineral resources of Riau has not yet felt the maximum because there are still many obstacles occur against IUP after UU No. 23 year 2014. Therefore, many things are judged from the performance of Mineral and coal unit at Department of energy and Mineral resources to find out the extent to which the performance of Mineral and coal unit of achieving the objectives of UU No. 23 year 2014. Knowing the performance of Mineral and coal Field unit at the Department of energy and Mineral resources of Riau (case study of IUP after UU No. 23 year 2014). Knowing the factors that hamper the performance of the Department of energy and Mineral resources of Riau (case study of IUP after UU No. 23 year 2014).The concept of the theory that researchers use is the employee performance according to theory of Hasibuan (2002:22). This research uses research methods qualitative with a study of descriptive data. In data collection, researchers using the technique of interviewing, observation, documentation, and library studies. The author uses the informant as a source of information and as a source of triagulasi techniques in the validity of the data.The results of this research show that the performance of the Mineral and coal unit are still not maximum, proved there are still constraints that are found during IUP in the service of Department energy and Mineral resources of Riau. Factors that affect the performance of Mineral and coal unit are UU No. 23 year 2014.Keywords: performance, Mining business license, Act No. 23 of 2014